Risk Stratification Score Improves Sensitivity for Advanced Colorectal Neoplasia in Colorectal Cancer Screening: The Oshima Study Workgroup. Issue 3 (2nd March 2021) - Sekiguchi, Masau; Kakugawa, Yasuo; Ikematsu, Hiroaki; Hotta, Kinichi; Konda, Kenichi; Tanaka, Yusaku; Takamaru, Hiroyuki; Yamada, Masayoshi; Sakamoto, Taku; Saito, Yutaka; Imai, Kenichiro; Ito, Sayo; et al.
Abstract : INTRODUCTION: Noninvasive colorectal cancer (CRC) screening methods with higher sensitivity for advanced colorectal neoplasia (ACN) than the fecal immunochemical test (FIT) alone are warranted. This study aimed to elucidate the diagnostic performance of a risk stratification score calculated using baseline individual characteristics and its combination with FIT for detecting ACN. METHODS: This cross-sectional analysis of data from a prospective cohort in Izu Oshima, Japan, included asymptomatic individuals age 40–79 years who underwent both 2-day quantitative FIT and screening colonoscopy. The 8-point risk score, calculated based on age, sex, CRC family history, body mass index, and smoking history, was assessed. Colonoscopy results were used as reference. RESULTS: Overall, 1, 191 individuals were included, and 112 had ACN. The sensitivity and specificity of the 1-/2-day FIT (cutoff: 50–200 ng Hb/mL) for ACN were 17.9%–33.9% (4.9%–22.0% for right-sided ACN) and 91.8%–97.6%, respectively. The risk score's c-statistic for ACN was 0.66, and combining the score (cutoff: 5 points) with 1-/2-day FIT (cutoff: 50–200 ng Hb/mL) yielded a sensitivity and specificity for ACN of 46.4%–56.3% (43.9%–48.8% for right-sided ACN) and 76.6%–80.8%, respectively. The specificity of the risk score and FIT combination for all adenomatous lesions was 82.4%–86.4%. DISCUSSION: The 8-point risk score remarkably increased the sensitivity for ACN, particularly for right-sided ACN. Although the specificity decreased, it was still maintained at a relatively high level. The risk score and FIT combination has the potential to become a viable noninvasive CRC screening option.